The role of digital banking management in modernizing payment methods and its impact on e-commerce operations - Redhouane, Fellag; Saidani, M’Hamed (International journal of economic perspectives, 2024)
The term electronic management has recently gained increasing traction, in parallel with its widespread adoption and the growing number of users. It has become an integral part of modern society, driving a technological and informational revolution across various aspects of social, economic, political, and recreational life. With this significant expansion, electronic management has become indispensable in banks and financial institutions, impacting traditional payment methods and leading to the emergence of electronic payment systems. These developments have, in turn, contributed to the enhancement and provision of high-quality banking services. This research paper aims to provide a conceptual and scholarly framework for electronic banking management and electronic payment methods, while examining their role in improving banking services and promoting electronic commerce.